2014
DOI: 10.1002/pon.3729
|View full text |Cite
|
Sign up to set email alerts
|

Why do oncology outpatients who report emotional distress decline help?

Abstract: Two common patient barriers to help with distress are a preference for self-help and a belief that distress is not sufficiently severe to warrant intervention. These beliefs were held by a sizeable proportion of individuals who reported very high levels of distress. Qualitative research and subsequent interventions for overcoming these barriers are required to obtain the most benefit from distress screening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
172
4
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(202 citation statements)
references
References 28 publications
(49 reference statements)
15
172
4
11
Order By: Relevance
“…This is consistent with findings demonstrating that only up to half of those with elevated distress perceived a need for using psychosocial support while a considerable proportion of one fifth to one fourth among those not distressed still felt such a need [4,8,9,15,36]. Although, in our study, current distress and previous use of support referred to different periods, barriers may have prevented cancer patients from utilization of psychological care, including lack of information about psychological services [37][38][39][40].…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with findings demonstrating that only up to half of those with elevated distress perceived a need for using psychosocial support while a considerable proportion of one fifth to one fourth among those not distressed still felt such a need [4,8,9,15,36]. Although, in our study, current distress and previous use of support referred to different periods, barriers may have prevented cancer patients from utilization of psychological care, including lack of information about psychological services [37][38][39][40].…”
Section: Discussionsupporting
confidence: 94%
“…Clover, Mitchell, Britton et Carter (2014) ont mené une étude afin de comprendre les raisons pour lesquelles les patients traités en ambulatoire qui rapportaient une détresse émotionnelle (4 et plus au TD) refusaient l'aide offerte. Dans cette étude 71 % de leur échantillon (N=311) ont refusé cette aide.…”
Section: Discussionunclassified
“…Clover, Mitchell, Britton, and Carter (2014) conducted a study to understand why patients in walk-in oncology clinics who reported emotional distress (4 and up on the DT) refused help. In their study, 71% of the sample (N=311) refused the help offered.…”
Section: Discussionmentioning
confidence: 99%